2018
DOI: 10.1080/1478422x.2018.1548410
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic corrosion of aluminium alloy members of bridge guiderails under severe atmospheric exposure conditions

Abstract: Aluminium alloys are nowadays preferred as materials for bridge guiderails especially for bridges connecting oceanic islands or spanning inlets due to their inherent corrosion resistance. But because of the limited mechanical strength of aluminium alloy, fasteners of guiderail members are made from steel materials. It has been found that contact between bare steel fasteners and aluminium alloy members can cause galvanic corrosion in the aluminium alloy. Research was carried out to investigate the capability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…During the first 24 h of immersion, the intercept of the LSV curves for aluminum and steel occurs on the anodic branch of aluminum, which exhibits the usual behavior for aluminum [18][19][20][45][46][47] showing the behavior of aluminum in this domain. However, after 48 h of immersion, the intercept happens on the cathodic branch of the aluminum LSV, between −0.90 and −1.20 V SCE, i.e., matching the oxygen reduction domain.…”
Section: Resultsmentioning
confidence: 81%
“…During the first 24 h of immersion, the intercept of the LSV curves for aluminum and steel occurs on the anodic branch of aluminum, which exhibits the usual behavior for aluminum [18][19][20][45][46][47] showing the behavior of aluminum in this domain. However, after 48 h of immersion, the intercept happens on the cathodic branch of the aluminum LSV, between −0.90 and −1.20 V SCE, i.e., matching the oxygen reduction domain.…”
Section: Resultsmentioning
confidence: 81%
“…The potential difference between the aluminium alloy and some dissimilar metal with which it is in contact has the effect of concentrating and accelerating Cl − attacks on contact areas and results in a corrosion type known as galvanic corrosion. Mrema et al [7] found that uncoated aluminium alloy members exhibit galvanic corrosion when they come in contact with untreated steel fasteners in an electrolytic environment and that the pits are concentrated around the contact area. In a larger scale project in 2013, the Durability Research Committee (Chairman: Y. Itoh) of Japan Aluminium Association carried out a survey of the condition of aluminium alloy guide rails on 14 bridges in Okinawa, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Mrema et al. [7] found that uncoated aluminium alloy members exhibit galvanic corrosion when they come in contact with untreated steel fasteners in an electrolytic environment and that the pits are concentrated around the contact area. In a larger scale project in 2013, the Durability Research Committee (Chairman: Y. Itoh) of Japan Aluminium Association carried out a survey of the condition of aluminium alloy guide rails on 14 bridges in Okinawa, Japan.…”
Section: Introductionmentioning
confidence: 99%